The design and implementation of Delta Inn Hotel e-reservation services / Nur Adyani Abdul Latiff - Abdul Latiff, Nur Adyani (2006)
The research report is about designing and implementing hotel e-reservation services with e-crm features and e-service quality dimension. There are four objective to be achieve which are to analyze e-crm features that can be include in hotel e-reservation services, to analyse user requirement of hotel e-reservation services. To design a hotel e-reservation services that are based on the user requirement and To develop a hotel e-reservation services with e-crm features. The approached that are used throughout this project development are through observing 40 hotel website in Malaysia to see the application of e-crm features in the website and conduct an interview with the manager of Delta Inn Hotel to capture requirement. From the analysis of the e-crm features, the adjustments of the features are made and as a result of the modification, lists of features that are suitable to apply in the hotel e-reservation services are obtained. As a result of the combination of user requirement and also from the features analysis, the development of the web is conduct to develop Delta Inn Hotel E-reservation Service that applies e-crm features.